Pest species of Macrolepidoptera in the Game Reserve of Velyka Dobron’ (Transcarpathia, Ukraine) - Szanyi, Szabolcs; Nagy, Antal; Molnár, Attila; Tóth, Miklós; Varga, Zoltán (Acta Agraria Debreceniensis, 2015)
The Game Reserve of Nagydobrony extends on a marginal area of a former peatland and is covered with extended hardwood gallery forests and oak-hornbeam forests and is surrounded by a mosaic-like agricultural landscape. Due to its richness of nature-like and semi-natural habitats it supports a diverse insect assemblage. By light and bait trapping 383 species of macro-moths were recorded from which larvae of 85 species are feeding either on forest trees and scrubs or on cultivated plants thus these can be considered as potential pest species. Thirteen species (mostly Geometridae and Erebidae: Lymantriinae) have a special significance for forestry due to defoliating activity in gradation periods. Considering the habitat connections, the composition of moth assemblage is dominated by generalist species with broad spectrum of ecological tolerance but the species connected with humid forested habitats are also richly represented. The bulk of species consists of widely distributed Euro-Siberian species, but also some Holo-Mediterranean species with more southern character and Mediterranean-Subtropical migrant species were registered. The bait trapping provided significant results on the phenology of the dominant species. The faunistically significant and/or protected species were observed in a low number of individuals only, thus the applied trapping methods did not damage the faunal composition.